2014
DOI: 10.1080/02671522.2014.887139
|View full text |Cite
|
Sign up to set email alerts
|

Teacher perspectives about lesson study in secondary school departments: a collaborative vehicle for professional learning and practice development

Abstract: Abstract:Two departments in a secondary school in England participated in 'lesson study' projects over a five-month period to explore its usefulness as a vehicle for professional development. Through a cycle of two research lessons, conducted separately in each department, teachers identified challenges that inhibited the learning of their students and collaboratively prepared innovative approaches to address the learning challenges. The process yielded multiple sets of data: DVD-recorded lessons, lesson plans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
0
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(87 citation statements)
references
References 30 publications
5
73
0
9
Order By: Relevance
“…According to the pre-service teachers, the ethos of the sessions was pleasant and motivating and they felt they were active members of the group. These findings are in line with those obtained by Cajkler et al (2015) with regard to a Lesson Study with beginning teachers and teachers of mathematics and modern languages, in which the participants also developed a sense of belonging to a professional community.…”
Section: Discussionsupporting
confidence: 90%
“…According to the pre-service teachers, the ethos of the sessions was pleasant and motivating and they felt they were active members of the group. These findings are in line with those obtained by Cajkler et al (2015) with regard to a Lesson Study with beginning teachers and teachers of mathematics and modern languages, in which the participants also developed a sense of belonging to a professional community.…”
Section: Discussionsupporting
confidence: 90%
“…Contextual Teaching and Learning model based on Lesson Study can also help students become easier in understanding the learning indicated by the increased learning outcomes in the cognitive domain (Fadillah et al, 2017). Lesson Study is able to develop the knowledge, abilities and professionalism of the teacher (Akiba, 2016;Cajkler, 2015)…”
Section: Resultsmentioning
confidence: 99%
“…In WALS International Conference 2016 in Exeter University-London at least 35 countries have called in for participation (Nurwidodo, 2016). Many countries in their attempt to transfer the Japanese model have developed their own perspectives on lesson study based on indigenous school cultures, educational context, and needs (Arani, Fukaya, & Lassegard, 2010;Cajkler, Wood, Norton, Pedder, & Xu, 2015).…”
Section: Introductionmentioning
confidence: 99%